Portfolio management in the conditions of globalization of financial markets - Bodau, Ualikhan; Mandel, Martin, 1962-; Táborský, František; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2025)
This thesis examines if international diversification is still applicable in the modern global financial markets, as growing integration has caused correlations between countries to rise. The research draws on 20 years of market data, comprising 1,834 international stocks, and involves simulations executed in Python for trying different combinations of portfolios by region and sector. The aim was to determine under what circumstances diversification would, in fact, minimize risk and if it still retains any value. The findings are that diversification within one market–i.e., the US–still reduces risk, particularly up to a certain number of assets. But the advantage of international diversification has diminished, largely because markets now move in tandem. That is not to imply, however, that in the situation of less volatile foreign than domestic markets, international diversification cannot enhance portfolio performance. Gold also served a beneficial purpose, always reducing risk and enhancing overall balance. The study illustrates that while the theory of diversification holds, its practice needs to be altered to accommodate the realities of global integration and evolving market dynamics.
Vedoucí práce: Martin Mandel
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: finance [obor bakal. práce]; bakalářské práce; bachelor's theses